A Novel Way to Prepare Hollow Sphere Ceramics. Issue 10 (24th July 2014) - Qi, Fei; Xu, Xingxing; Xu, Jie; Wang, Yali; Yang, Jinlong; Colombo, P.
<x xml:space="preserve">Abstract</x> Recent developments in the fabrication of hollow spheres have allowed our group to prepare a new type of macroporous ceramics: hollow sphere ceramics (HSCs). Alumina hollow spheres were first produced by centrifugal spray‐drying of particle‐stabilized foam slurry. The obtained hollow spheres were sintered together to form HSC at high temperatures. The effect of the sintering temperature on the linear shrinkage, porosity and compressive strength of HSC samples was investigated. When the sintering temperature was increased from 1400°C to 1600°C, the samples shrunk increasingly and the porosity decreased from 59% to 42%, which lead to an increase in the strength of the alumina foams from 6.9 (at 1400°C) to 100.0 MPa (at 1550°C). The mechanical strength of the HSC highly depends on the contact area between the hollow spheres, which could be increased by increasing the sintering temperature, decreasing the size of hollow spheres or by slurry infiltration.